Рахиль: Роман с клеймами / А. Геласимов - Геласимов Андрей (Граффити, 2004)
Экземпляры: (20181023) / Инвентарный номер: 41049 / Цена: 112.50 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 31 / ББК: 84(2Рос=Рус)6